Taxonomic review of genus Sooretamys Weksler, Percequillo & Voss (Rodentia: Cricetidae: Sigmodontinae): an integrative approach. (August 2014) - de Almeida Chiquito, Elisandra; D'Elía, Guillermo; Percequillo, Alexandre Reis
<x xml:space="preserve">Abstract</x> Sooretamys is a monotypic genus of the family Cricetidae, subfamily Sigmodontinae, that is distributed throughout eastern South America in the Atlantic Forest Biome, including Argentina, Brazil, and Paraguay. The taxonomic history of the forms associated with this genus is long and relatively complex, and few studies have evaluated the taxonomic problems of this genus. To this end, our goal was to describe the degree and geographical pattern of morphological and molecular variation in this genus to test the current hypothesis that the genus is monotypic, and, as a consequence, to determine the status of the nominal forms associated with Sooretamys. Accordingly, we employed morphometric, morphological, and molecular tools, according to an integrative taxonomy approach. The results show that some level of morphometric discontinuity is present between the individuals from Paraguay and those from adjacent localities in Brazil and Argentina; sharp discontinuities were not observed in qualitative traits. Molecular analyses of the mitochondrial cytochrome b gene showed that the Paraguayan populations have some degree of genetic differentiation, but the haplotypic variants do not form a monophyletic group. Thus, the evidence so far suggests a difference in the genes and morphology of the Paraguayan population, but there is no consistent resolution (e.g. lack of monophyly) to show that specimens from Paraguay represent a distinct population that would merit taxonomic recognition. Thus, we recognize a single species within the genus Sooretamys, named Sooretamys angouya. The pattern of morphological and genetic differentiation of Sooretamys could be the result of divergence with gene flow. However, our data also correspond in some aspects with the model advanced by Carnaval & Moritz, which claims the existence of stable Atlantic Forest areas where the forest biota persisted during the Quaternary climatic fluctuations. Whatever process has occurred, S. angouya represents one species with a complex evolutionary history, and the analysis of additional samples would be welcome to further elucidate the process of diversification of this taxon. © 2014 The Linnean Society of London